KHI DAN KONFIGURASI POLITIK HUKUM ORDE BARU (Vis a Vis Antara Hukum Islam dan Sistem Pemerintahan Otoriter) - Munif, Nasrulloh Ali (Ahkam: Jurnal Hukum Islam, 2015)
The discussion about the Compilation of Islamic Laws (KompilasiHukum Islam/KHI) never ends. There are differences among scholarsin comprehending the texts because such compilation was issued inthe New Order regime. In the constellation of the KHI, the productof the law appears in semi-responsive strategy. In addition, in theKHI there is a reduction of the law to a certain limit in the contextof law in the country. The But political configuration Islamic lawalso brings impacts on the domination each other in the New Orderpolitical coniguration.Kata kunci: Kompilasi Hukum Islam, Konfigurasi Politik, Orde Baru,dan Otoriter